SCOTUS 2020
XII, 176 p. 2 illus., 1 illus. in color.
Keywords: Each year, the Supreme Court of the United States announces new rulings with deep consequences for our lives. This third volume in Palgrave’s SCOTUS series describes, explains, and contextualizes the landmark cases of the US Supreme Court in the term ending 2020. With a close look at cases involving key issues and debates in American politics and society, SCOTUS 2020 tackles the Court’s rulings on LGBT discrimination, abortion regulation, subpoenas of the Trump administration, the Electoral College, DACA and presidential power, Native rights, cross-border rights, the Second Amendment, church and state, separation of powers, criminal justice, and more. Written by notable scholars in political science and law, the chapters in SCOTUS 2020 present the details of each ruling, its meaning for constitutional debate, and its impact on public policy or partisan politics. Finally,SCOTUS 2020 offers an analysis of the current state of ideological and interpretive divisions on the Court. Morgan Marietta is Associate Professor of Political Science at the University of Massachusetts Lowell, USA.